Determinants of Residential Consumers Acceptance of a Utility-Scale Battery Energy Storage System in Malaysia: Technology Acceptance Model Theory from a Different Perspective - Jaaffar A.H.; Majid N.A.; Alrazi B.; Ramachandaramurty V.K.; Dahlan N.Y. (MDPI, 2023)
Battery storage; Developing countries; Housing; Battery energy storage systems; Consumer acceptance; Consumer attitudes; Malaysia; Malaysians; Model theory; Residential consumers; Technology acceptance model; Technology acceptance model theory; ]+ catalyst; Electric batteries